Positive Organizational Change. (December 2014) - Cameron, Kim; McNaughtan, Jon
For 50 years, JABS has played a significant role in making available new knowledge about organizational change. In the last decade, JABS has once again been at the forefront of introducing a new approach to organizational change, namely, positive organizational scholarship and positive organizational change. This article summarizes some of the findings that have emerged from this new approach to change, and its most important attributes are identified.